Anisotropic Photoluminescence of Poly(3-hexyl thiophene) and Their Composites with Single-Walled Carbon Nanotubes Highly Separated in Metallic and Semiconducting Tubes - Mihaela Baibarac; Grigory Arzumanyan; Monica Daescu; Adelina Udrescu; Kahramon Mamatkulov (Molecules, 2021)
In this work, the effect of the single-walled carbon nanotubes (SWNTs) as the mixtures of metallic and semiconducting tubes (M + S-SWNTs) as well as highly separated semiconducting (S-SWNTs) and metallic (M-SWNTs) tubes on the photoluminescence (PL) of poly(3-hexyl thiophene) (P3HT) was reported. Two methods were used to prepare such composites, that is, the chemical interaction of the two constituents and the electrochemical polymerization of the 3-hexyl thiophene onto the rough Au supports modified with carbon nanotubes (CNTs). The measurements of the anisotropic PL of these composites have highlighted a significant diminution of the angle of the binding of the P3HT films electrochemical synthetized onto Au electrodes covered with M + S-SWNTs. This change was attributed to metallic tubes, as was demonstrated using the anisotropic PL measurements carried out on the P3HT/M-SWNTs and P3HT/S-SWNTs composites. Small variations in the angle of the binding were reported in the case of the composites prepared by chemical interaction of the two constituents. The proposed mechanism to explain this behavior took into account the functionalization process of CNTs with P3HT. The experimental arguments of the functionalization process of CNTs with P3HT were shown by the UV-VIS-NIR and FTIR spectroscopy as well as surface-enhanced Raman scattering (SERS). A PL quenching process of P3HT induced both in the presence of S-SWNTs and M-SWNTs was reported, too. This process origins in the various de-excitation pathways which can be developed considering the energy levels diagram of the two constituents of each studied composite.